JAK inhibition ameliorated experimental autoimmune encephalomyelitis by blocking GM-CSF-driven inflammatory signature of monocytes - Shuai Shao; Chengjuan Chen; Gaona Shi; Yu Zhou; Yazi Wei; Lei Wu; Lan Sun; Tiantai Zhang (Elsevier, 2023)
Monocytes are key effectors in autoimmunity-related diseases in the central nervous system (CNS) due to the critical roles of these cells in the production of proinflammatory cytokines, differentiation of T-helper (Th) cells, and antigen presentation. The JAK-STAT signaling is crucial for initiating monocytes induced immune responses by relaying cytokines signaling. However, the role of this pathway in modulating the communication between monocytes and Th cells in the pathogenesis of multiple sclerosis (MS) is unclear. Here, we show that the JAK1/2/3 and STAT1/3/5/6 subtypes involved in the demyelination mediated by the differentiation of pathological Th1 and Th17 and the CNS-infiltrating inflammatory monocytes in experimental autoimmune encephalomyelitis (EAE), a model for MS. JAK inhibition prevented the CNS-infiltrating CCR2-dependent Ly6Chi monocytes and monocyte-derived dendritic cells in EAE mice. In parallel, the proportion of GM-CSF+CD4+ T cells and GM-CSF secretion were decreased in pathological Th17 cells by JAK inhibition, which in turns converted CNS-invading monocytes into antigen-presenting cells to mediate tissue damage. Together, our data highlight the therapeutic potential of JAK inhibition in treating EAE by blocking the GM-CSF-driven inflammatory signature of monocytes.